Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s43042-019-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant p16 methylation as an early diagnostic marker in blood of hepatocellular carcinoma patients

Abstract: Background Alpha-fetoprotein (AFP) is currently used for serologic screening in hepatocellular carcinoma (HCC) but with low sensitivity ranging 41–65% with a high rate of false-negative and false-positive results. For the hypermethylation of the p16 inhibitor of cyclin-dependent kinase 4 (p16INK4A), a tumor suppressor gene results in the uncontrolled division of cells. This suggests that the loss of p16INK4A function due to promoter methylation may be an early event in HCC pathogenesis so the study aimed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…As regards AFP serum levels, there was no significant association with CDKN2A methylation, in contrast to Seif et al, who observed that AFP serum levels were considerably higher in the methylated group of patients than in the non-methylated group [7]. The current study's findings might be related to the diversity of the patient groups evaluated.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As regards AFP serum levels, there was no significant association with CDKN2A methylation, in contrast to Seif et al, who observed that AFP serum levels were considerably higher in the methylated group of patients than in the non-methylated group [7]. The current study's findings might be related to the diversity of the patient groups evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…Cell cycle regulation, apoptosis induction, microtubule stability, and cellular adhesion are all functions of the protein encoded by RASSF1A [9]. According to previous research, RASSF1A deactivation by promoter hypermethylation has been found to occur frequently in malignant tumors, including HCC [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation